A Comparative Case Study on Process Optimization and the Modern Law Library's Involvement in Achieving Efficiency at the Law School in Times of Change. Issue 2 (23rd November 2020) - Wittman, Jessica de Perio; Brown, Kathleen (Katie)
Abstract: Law firms have been utilizing process optimization tools, such as Lean Six Sigma, to improve internal processes and build efficiencies. Successful outcomes require leadership teams that believe that process improvement is more than just a tool kit to solve problems or a collection of methodologies and processes. Through collection development practices, continuous learning opportunities, and the use of cross-functional teams, the modern law library has effectively demonstrated its ability to meet the dynamic needs of the law school community. Similarly, law librarians find themselves uniquely positioned to collaborate with law school administration on continual process improvement strategies in times of change. This article will provide a foundation on process optimization methodologies, such as Lean Six Sigma, Agile, and Legal Lean, as well as the application of those tools and techniques in various fields. Finally, the article asserts that law schools should adopt process optimization techniques and leverage their law libraries to improve business processes and operations at their respective institutions.